Pengembangan Pengembangan E-Modul Pembelajaran Berhemat Energi Berbasi Visual Auditory Kinesthetic (VAK) Untuk Siswa Kelas IV Sekolah Dasar - Bria, Maria Angelina Yolanda; I Ketut Gading (Universitas Pendidikan Ganesha, 2023)
Lack of teacher ability to develop teaching materials causes boredom. The aim of this research is to develop a Visual Auditory Kinesthetic (VAK) based learning e-module aimed at students in the fourth grade of elementary school, a solution that researchers can offer. This research is a mixed method-based development research using the 4 D (Four-D) research model. Data collection methods use observation, interviews and questionnaires. The research subjects were 4 experts and 1 teacher. The test subjects were shown to fourth grade elementary school students. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results show that material experts and media experts carry out product testing, while teachers and students carry out assessments. The results show overall results for material experts are 91 percent in the very good category, overall media experts are 89 percent in the very good category, practitioners overall are 95 percent in the very good category, and students overall are 93 percent in the very good category. Therefore, it can be concluded that learning e-modules that focus on energy-saving materials for fourth grade elementary school students are suitable for use. The implication of this research is that this learning e-module can help teachers and students as a learning tool to support learning, especially in energy saving material.